The Changing Trends of Corporate Social and Environmental Disclosure within the Australian Gambling - Loh, Ricci; Deegan, C.; Inglis, R. (Wiley-Blackwell Publishing Asia, 2014)
This study examines how the corporate social and environmental disclosure (CSD) practices of a sample of gambling companies operating within Aust ralia appears to change aro und the time of three speci?c interrelated Australian government initiatives; the Productivity Commi ssion, 1999, Australia's Gam bling Industries, Report No. 10, the subsequent establishment of the Ministerial Council on Gambling and the MCG-initiated Nat ional Framework on Problem Gambling. Drawing upon three complementary theories, namely legitimacy, stakeholder and institutional theory, our analysis of the extent and type of CSD in the annual reports of gambling companies over a 15 year period suggests that CSD is a response to social pressures created around the time of these initiatives